Ameloblastic fibro-odontoma or complex odontoma masquerading as gingival enlargement - Doddabasavaiah Basavapur Nandini; Praveen Bokka Reddy; Waikhom Robindro Singh; Koijam Sashikumar Singh (Wolters Kluwer Medknow Publications, 2021)
Ameloblastic fibro-odontoma is a rare tumor affecting the pediatric population and young adults. The World Health Organization (WHO) in 2005 defined it as "A neoplasm composed of proliferating odontogenic epithelium in a cellular ectomesenchymal tissue with varying degrees of inductive changes and dental hard tissue formation." There exists a controversy on its histogenesis designating it as a hamartoma (developing complex odontoma [CO]) or a true neoplasm since both the lesions appear similar histologically. Recently, the WHO in 2017 has clubbed both these lesions as the same entity. Most cases are reported in males and in mandible, while cases in maxilla are scarce. This article describes a recurrence of a previously reported case of ameloblastic fibroma which showed maturation into AFO or CO in a girl aged 6 years in the posterior maxilla. This case is reported due to its rarity and a brief review with differential diagnosis is also discussed.